2013
DOI: 10.1007/978-3-642-41924-9_38
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Strategy-Oriented Value Modeling Language: Identifying Strategic Elements of the VDML Meta-model

Abstract: Abstract. The concept of value is increasingly important in organizations. This has led to the creation of value models that capture internal value creation and the external exchange of value between the company and its value network. To facilitate strategic alignment, the meta-model specification of value modeling languages should both fully reflect the strategic choices of a company and define 'what' a company must do to realize value creation. In this paper, the Value Delivery Modeling Language (VDML) meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This paper finishes the development of a focused BM representation. Previous research already identified the components of a BM (Roelens and Poels 2013b) and investigated whether relevant enterprise modeling languages capture these components (Roelens and Poels 2013a). This resulted in a set of VDML meta-model constructs that cover the complete BM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper finishes the development of a focused BM representation. Previous research already identified the components of a BM (Roelens and Poels 2013b) and investigated whether relevant enterprise modeling languages capture these components (Roelens and Poels 2013a). This resulted in a set of VDML meta-model constructs that cover the complete BM.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards enterprise modeling languages (i.e., the REA value chain and value system specification, VNA, capability maps, e 3 -value, e 3 -forces, and VDML) that are used for representing BMs, were reviewed (Roelens and Poels 2013a). It was analyzed which components of the framework were covered by these representations.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations